Plasma B-type natriuretic peptide is independently associated with cardiovascular events and mortality in patients with chronic kidney disease - Hiroyuki Hayashida; Naoki Haruyama; Akiko Fukui; Ryota Yoshitomi; Hironobu Fujisawa; Masaru Nakayama (Scientific Reports, 2024)
Abstract The association between B-type natriuretic peptide (BNP) and cardiovascular (CV) events and mortality has not been well characterized in patients with chronic kidney disease (CKD). We prospectively investigated whether BNP was associated with CV events or mortality beyond cardiac alterations in 1078 patients with CKD. Participants were divided into the following 3 groups according to circulating BNP concentration: < 40 pg/mL, low; 40–100 pg/mL, middle; and > 100 pg/mL, high. Primary outcome was fatal or nonfatal CV events, and alternative outcome was a composite of fatal or nonfatal CV events, or non-CV deaths. During a median follow-up of 2.6 years, CV and composite events occurred in 158 and 248 participants, respectively. Cox analyses after adjustment for covariates, including cardiac parameters, showed that the hazard ratios (HRs) (95% confidence intervals [CIs]) for CV events of middle and high groups were 1.00 (0.63, 1.58) and 1.72 (1.06, 2.79), respectively, compared with low group. Additionally, similar results were obtained for composite events; the HRs (95% CIs) of middle and high groups were 1.10 (0.77, 1.57) and 1.54 (1.04, 2.27), respectively, compared with low group. Thus, in CKD, high BNP concentrations were independently associated with CV events and mortality, independent of cardiac alterations.